2001
DOI: 10.1074/jbc.m008985200
|View full text |Cite
|
Sign up to set email alerts
|

THIK-1 and THIK-2, a Novel Subfamily of Tandem Pore Domain K+ Channels

Abstract: Two cDNAs encoding novel K؉ channels, THIK-1 and THIK-2 (tandem pore domain halothane inhibited K ؉ channel), were isolated from rat brain. The proteins of 405 and 430 amino acids were 58% identical to each other. Homology analysis showed that the novel channels form a separate subfamily among tandem pore domain K ؉ channels. The genes of the human orthologs were identified as human genomic data base entries. They possess one intron each and were assigned to chromosomal region 14q24.1-14q24.3 (human (h) THIK-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
171
2
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(193 citation statements)
references
References 32 publications
(46 reference statements)
6
171
2
2
Order By: Relevance
“…In cerebellar granule cells (Millar et al, 2000) and cranial motoneurons (Talley et al, 2000) receptor-mediated inhibition of TASK-1 has been reported, which suggests an important role for the TASK family of K 2p channels in neuromodulation. Experiments testing functional expression of TASK-5 and THIK-2 have been unsuccessful to date (Ashmole et al, 2001;Rajan et al, 2001) and so their biophysical properties remain undefined. However, sequence homology and similarities in topology with other K 2p channel family members strongly suggests conserved function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cerebellar granule cells (Millar et al, 2000) and cranial motoneurons (Talley et al, 2000) receptor-mediated inhibition of TASK-1 has been reported, which suggests an important role for the TASK family of K 2p channels in neuromodulation. Experiments testing functional expression of TASK-5 and THIK-2 have been unsuccessful to date (Ashmole et al, 2001;Rajan et al, 2001) and so their biophysical properties remain undefined. However, sequence homology and similarities in topology with other K 2p channel family members strongly suggests conserved function.…”
Section: Discussionmentioning
confidence: 99%
“…The ten transcripts were shown to be expressed in the rat IC, representing four groups from the six classes of K 2p channel subunits, divided based on some differences in sensitivities (Lesage et al, 2000;Rajan et al, 2001;Goldstein et al, 2001;Patel et al, 2001). This suggests that neurons in the inferior colliculus are sensitive to the associated modalities and that the intrinsic excitability of IC neurons can be modulated by multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…Three cloned mammalian two-pore channels, KCNK7, KCNK13, and KCNK15, have not produced K ϩ currents when expressed in a heterologous system, suggesting that association with other proteins may be necessary for their functioning (Rajan et al, 2001). Similarly, we have been unable to obtain K ϩ currents from SUP-9 or SUP-9(n1550), expressed alone or together with SUP-10 and UNC-93, in Xenopus oocytes or human embryonic kidney (HEK) cells using whole-cell voltage-clamp configuration, although our control experiments demonstrated a robust K ϩ activity from the mammalian rat TASK-1 channel expressed in both cell types (Perez de la Cruz and Horvitz, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…The subunits are divided into six groups or classes based on different sensitivities to various modulators. To date, attempts at functional expression (Ashmole et al, 2001;Rajan et al, 2001) of TASK-5 and THIK-2 have failed so their biophysical properties are undefined. However, sequence homology and similarities in topology with other family members strongly suggests conserved function.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of several subunits have been mapped throughout the brain using in situ hybridization Rajan et al, 2001;Talley et al, 2001). The TASK-5 subunit is selectively expressed at high levels in auditory brain stem neurons and Purkinje cells of the cerebellum, with no detection in other labeled brain regions except for a few neurons in the spinal trigeminal nucleus, the mammillary nucleus and the olfactory bulb.…”
Section: Introductionmentioning
confidence: 99%